2013
DOI: 10.12697/fce.2013.50.03
|View full text |Cite
|
Sign up to set email alerts
|

New records of lichen species from western Mongolia

Abstract: New records of lichens are compiled for the Mongolian Altai and the Khangai, western Mongolia. All records are from the forest-steppe. A total of 31 species are reported for the first time from the Mongolia Altai and another 18 species are new for the Khangai.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…3A). It has also been reported from a site in western Mongolia, just west of the mapping area, by Hauck et al (2013). This saxicolous species is well characterized by its relatively small ascospores with type B development (but the development type is often difficult to find) and septal swelling in KOH, therefore belonging to the Dirinaria-type (Sheard 2010).…”
Section: Rinodina Endospora Sheardmentioning
confidence: 89%
See 3 more Smart Citations
“…3A). It has also been reported from a site in western Mongolia, just west of the mapping area, by Hauck et al (2013). This saxicolous species is well characterized by its relatively small ascospores with type B development (but the development type is often difficult to find) and septal swelling in KOH, therefore belonging to the Dirinaria-type (Sheard 2010).…”
Section: Rinodina Endospora Sheardmentioning
confidence: 89%
“…This species is broadly distributed across Scandinavia and Siberia and is scattered in montane localities in the Southern Alps, Asia Minor and western North America (Mayrhofer & Sheard 2007). It has been widely reported from the Russian Far East (Chabanenko 2002) and from western Mongolia by Hauck et al (2013).…”
Section: Rinodina Septentrionalis Malmementioning
confidence: 94%
See 2 more Smart Citations
“…Outside Europe, Lithocalla ecorticata has been reported from India (Bajpai et al 2018; zeorin reported as present or absent), Mongolia (Hauck et al 2013; zeorin reported), Borneo (Paukov et al 2017), Canada (Laundon 2003; chemistry not stated), Chile (Kukwa 2006; chemistry not specifically stated but material from Poland was reported to have zeorin), China (Kukwa 2006) and Antarctica (Øvstedal & Lewis Smith 2004). pointed out that Leprocaulon knudsenii Lendemer & B.P.…”
Section: (Figs 3 and 4)mentioning
confidence: 99%